2007
DOI: 10.1007/s00264-007-0453-3
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of internal fixation and prosthesis replacement for radial head fractures of Mason type III

Abstract: Although several treatment options for radial head fractures are available, no clear solutions exist. In this study we therefore compare open reduction and internal fixation (ORIF) with bipolar radial head prosthesis replacement in treatment of radial head fractures of Mason type III. Cement stem and bipolar radial prosthesis were used to treat 12 fresh cases and two old cases of Mason type III radial head fracture. As a control group, another eight cases of radial head type III fracture were treated with ORIF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0
17

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(76 citation statements)
references
References 12 publications
1
58
0
17
Order By: Relevance
“…The radial head prosthesis (RHP) seems preferable to osteosynthesis in Mason type III fracture with more than three fragments [17]. Primary prosthetic radial head replacement is indicated in non-reconstructable three-or more fragment radial head fractures with valgus instability and further concomitant injuries.…”
Section: Introductionmentioning
confidence: 99%
“…The radial head prosthesis (RHP) seems preferable to osteosynthesis in Mason type III fracture with more than three fragments [17]. Primary prosthetic radial head replacement is indicated in non-reconstructable three-or more fragment radial head fractures with valgus instability and further concomitant injuries.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [31] concluded that metallic radial head replacement gave better joint function that ORIF. Ruan et al [32] concluded that bipolar radial head replacement was better than ORIF. Boulas [33] concluded that, when possible, ORIF provided better functional results than silastic replacement.…”
Section: Discussionmentioning
confidence: 99%
“…They therefore recommended arthroplasty in these complicated comminuted fractures as it produced consistent results and was more straightforward than fixation. Considering these reviews, it is evident that the lack of detail regarding baseline characteristics of patients in the studies by Chen [31] , Ruan [32] and Boulas [33] is a major weakness. This is another limitation of this search strategy.…”
Section: Discussionmentioning
confidence: 99%
“…2). Although nonunion is not a very common complication of the treatment consisting in fracture reduction and fixation, it is still described by most authors publishing ORIF outcomes in radial head fractures [13,19,20]. It seems to 40-letnia kobieta, u której, najprawdopodobniej z powodu niewystarczająco stabilnego zespolenia dużego (około 20% powierzchni) fragmentu głowy kości promieniowej, doszło do jego przemieszczenia i w konsekwencji do braku zrostu (Ryc.…”
Section: Dyskusjaunclassified
“…2). Brak zrostu, choć nie jest bardzo częstym powikłaniem po nastawieniu i zespoleniu, to jednak nadal jest opisywany przez większości autorów publikujących wyniki po ORIF złamań głowy kości promieniowej [13,19,20]. Wydaje się, iż najważniejszą rolę w unikaniu tego powikłania pełni stabilne zespolenie wszystkich odłamów złamania.…”
Section: Dyskusjaunclassified